Social Cognition: The Key Factor Predicting Social Outcome in People with Schizophrenia? - Harvey, Philip D. (Matrix Medical Communications, 2010)
Impairments in different cognitive abilities have been found to be correlated with reduced real-world functioning in people with schizophrenia. A number of other features of the illness, such as depression and negative symptoms, contribute to the overall prediction of these outcomes. Impairment in social cognition is of particular interest as a mediating influence between cognition and social outcomes. Social cognition is a set of cognitive processes applied to the recognition, understanding, accurate processing, and effective use of social cues in real-world situations. In schizophrenia research, social cognition comprises the following domains: emotion perception, theory of mind (ToM), and attributional style. While substantial research has indicated that these abilities are clearly related to social outcomes, research has been slowed by problems in the measurement of these abilities. In this article, I will describe these abilities, discuss how they are currently measured, and how research could improve the current measurement of these abilities to make them more clinically useful.